If f(x)=1/9x-2
then f^-1(x) will be
lets assume f(x)=y
y=1/9x-2
y+2=1/9x
9(y+2)=x
f^-1(x)=9(y+2)
rest u can do with the same method
3.
ninths=1/9
1/3 is equal to 3/9.
so (1/9)*3 = 3/9
Let x be the old price
X= 1200$
The price decreased 20% after 1 year to become price y :
Y= 0.8x
= 0.8 (1200)
= 960$
In the year after y also decreased 20% to be price y’:
Y’= 0.8y
= 0.8 (960)
= 768 $
The price y’ then decreased 20% to become price y’’:
Y’’ = 0.8 y’
= 0.8 (768)
= 614.4 $
Then the price will be 614.4 $ after 3 years
I need a picture of the figures to help with this!
Answer:
5 2/10
Step-by-step explanation: